KAJIAN SOSIAL BUDAYA SERAT CANDRARINI MASA PAKU BUWONO IX (1861-1893) - Puspitasari, Dwi (Candi, 2014)
The objectives of article were: (1) to find out the social-cultural background of Serat Candrarini, (2) to find out the content and the effect of Serat Candrarini in Kasunanan Surakarta Palace?s life during the reign of Paku Buwono IX, and (3) to find out the relevance of content and the effect of Serat Candrarini in Local History course in College.This research employed historical method. The data sources used particularly were primary and secondary sources. Technique of collecting data used was historical analysis one. The data analysis used historical technique.Result of this research stated: (1) the emergence of serat candrarini was due to condition of social and culture. Such as many polygamy that happened and due to people from lower class until higher class. (2) Serat Candrarini described physic, characters, and behavior of Arjuna five wives that show how the attitude and behavior of women so the marriage life maintained although she become co-wives. (3) Result of this research has a dictated aim that can be applied in polygamy household life or education, especially in collage.Keywords: Javanese Women, Serat Candrarini, Lesson